Use of Cystatin C Biomarker in Patients with Possible Renal Failure - Alexander Benavides Couto; Yamila Rodríguez Jiménez; Dellys González Borges; Idalmis Luisa Martinez Serrano; Ibis Hernandez Palet; Belkis Rosa Vilaboy Perez (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Renal injury is a frequent complication in hospitalized and outpatients and its incidence has increased in recent years, either as a primary disease or as a secondary diagnosis. Early detection of kidney disease in its milder degree would be beneficial to begin treatment for better results. This literature review, based on the analysis of about 30 scientific articles, describes the feasibility of using cystatin C as a renal biomarker; it also refers to the advantages and limitations that its use reports within the clinical bioanalysis; and finally the importance of the future use of cystatin C as an analytical biomarker in different laboratories of the health system in Cienfuegos. This work provides relevant information about health personnel´s updating and training in medical conditions which may be detected at the molecular and cellular level.